P186 Outcomes of maintenance ustekinumab therapy for Crohn's disease based on inflammatory burden: A post-hoc analysis of the UNITI trials. (16th January 2018) - Ghosh, S; Sattin, B; Tornatore, V; Gasink, C; Gao, L -L; Sloan, S; Rutgeerts, P; Sands, B; Hanauer, S; Feagan, B
Abstract: Background: Patient inflammatory burden has been postulated to predict response to anti-inflammatory therapies. Ustekinumab(UST) is the only approved anti-IL-12/23 mAb for the treatment of Crohn's disease (CD) and the PBO-controlled UNITI registration trials present an opportunity to test this hypothesis. We evaluated clinical outcomes to 90 mg q8 and q12wk SC treatment strategies based on inflammatory biomarkers C-reactive protein (CRP) and fecal calprotectin (fCal). Methods: In UNITI 1 (anti-TNF therapy failures) and UNITI 2 (conventional therapy failures), patients were randomised to PBO, UST 130 mg IV, or UST ~6mg/kg IV. At 8weeks, all responders to IV induction therapy participated in IM-UNITI and were randomised to SC maintenance treatment with PBO, UST 90 mg q8wks, or UST 90 mg q12wks. Clinical endpoints were assessed after 44 weeks of maintenance therapy. Results were stratified by inflammatory burden based on CRP and fCal. For CRP, inflammatory burden categories used were ≤5, >5 and ≤10, and >10 mg/l. For fCal, inflammatory burden categories used were <250 and ≥250 mg/kg. Results: When patients were stratified by inflammatory burden at baseline (BL) of induction (i.e. before IV dose), CRP thresholds discriminated patients in the 90 mg q12wk group into those more or less likely to achieve clinical endpoints at wk44 of maintenance. This finding is also supported by fCal stratification at BL of induction (i.e. before IV dose).Stratification at BL of maintenance provides greater distinction between UST doses. Maintenance week44 results stratified by CRP are shown in Figure 1. They suggest that a CRP >10 mg/l at maintenance BL (i.e. before first SC dose) discriminates a high inflammatory burden population that benefited from UST 90 mg SC q8wk dosing vs. q12wk dosing. Response and remission rates were similar between UST SC q8wk and q12wk dosing in patients with maintenance BL CRP ≤5mg/l and between 5and10 mg/l. Similar effects were seen at maintenance wk44 endpoints using fCal (Figure 2). Those with a higher inflammatory burden(fCal >250 mg/kg) at maintenance BL more clearly separated from PBO in q8wk group(56.4% vs. 33.8% remission, p = 0.002) vs. q12wk group (46.1% vs. 33.8% remission, p = 0.065). Conclusions: CD patients with low inflammatory burden based on biomarkers CRP and fCal at BL and/or at initiation of maintenance therapy can benefit from q8 or q12wk maintenance dosing with UST, while those with high inflammatory burden are likely to need q8wk to maintain benefit.